Spatial and temporal distribution of a marine microbial parasite, Syndiniales MALV I and II, within St Helena Bay - Fourie, Shani (Department of Biological Sciences, 2025)
MALV I and II are globally distributed marine microbial parasites that infect and kill a wide range of phytoplankton hosts. These organisms play an important role in bloom dynamics, are suspected to terminate algal blooms, and contribute significantly to carbon fluxes, an important process required to lock away greenhouse gases. The study aims to investigate the spatial and temporal distribution of MALV I and II and their hosts in the Benguela upwelling system, one of the four major Eastern Boundary Upwelling Systems (EBUS). A Fluorescent In Situ Hybridization (FISH) technique was used to identify and quantify MALV I and II in samples taken at 0m and 10m respectively over the course of 10 consecutive days during an upwelling event in December of 2016, and in samples taken at 1m and 25m respectively over the course of 5 consecutive days during a stratified period in April 2019 within St Helena Bay. Microscopy observations revealed a distinct difference in their infection dynamics between an active upwelling season (austral spring and summer) and a stratified period (austral autumn and winter), with distinctly different phytoplankton communities present in the water column between these two seasons. Whilst temperature and silicate were significant factors correlating with the infection rates at the surface during an upwelling period, biological factors (presence of MALV I and II hosts) appeared to be the most important contributor. Furthermore, 18S rRNA data confirmed that MALV I and II dominated the water column, with group I exhibiting the highest relative abundance, contradicting microscopy observations which showed no significant difference in infection rates between MALV I and II. This shed light on the realities of amplicon data, especially with high gene copy numbers present in MALV rRNA. This study applies a holistic approach to understanding the infection dynamics of MALV I and II and in doing so revealed a transition from diatom hosts during an active upwelling period to dinoflagellate hosts during a stratified period in the same region. Ultimately, the MALV I and II populations are dependent upon available hosts to infect, and the infection rates are driven by multiple environmental and biotic factors.